(untitled) (REVISTA NODO, 2026)
Artistic creation and scientific research constitute two fundamental pillars in the construction of human knowledge. In recent decades, a significant epistemological transformation has challenged the traditional division between them, leading instead to a more nuanced examination of their interrelationship. The primary objective of this research is to explore and problematize the existing relationships between these two endeavors through the analysis of documentary sources and the authors’ reflections on their own experience as researchers and creators. The most relevant findings suggest that artistic creation and research generate both cognitive and aesthetic knowledge.